Understanding Additives - Müller, Bodo (Vincentz Network, 2019)
This book covers everything about the mode of action, application and possible side effects of the most important coatings additives - in a single volume, presented in a textbook style. It reflects the needs of practical work - thus it enables the reader to rapidly gain a solid grounding in these critical, yet complex constituents of all paint formulations. It provides both an overview and in-depth basic knowledge of the most important classes of additives. The various types of damage eliminated or prevented by additives are vividly illustrated with colour photos. An indispensable companion for formulators!